Studi Kuantitatif Kerapatan Lamun di Perairan Teluk Cempi: Implikasi untuk Konservasi dan Manajemen Sumber Daya Laut: Quantitative Study of Seagrass Density in the Waters of Cempi Bay: Implications for Conservation and Management of Marine Resources - Lestariningsih, Wiwid Andriyani; Himawan, Mahardika Rizqi; Santika, Lora; Gigentika, Soraya; Wibisono, Rendy Vidya; Hernawati, Hernawati; Himawan, Cahya (LPPM Universitas Mataram, 2023)
Cempi Bay is an important water area with a rich and diverse ecosystem. One crucial component of marine ecosystem that plays a major role in maintaining the balance of the marine environment is seagrass. The objective of this research is to provide critical insights into the dynamics of seagrass populations in Cempi Bay and offer an overview of the broader coastal ecosystem's condition. The research, conducted in June-July 2021 at 5 research stations, employed the transect method. At each data collection point, three transect lines were created perpendicular to the coastline. The distance between transect lines was 100 m, and each transect consisted of 10 quadrants measuring 1x1 m with a 5 m distance for each quadrant. Four seagrass species were identified: Thalassia hemprichii, Cymodocea rotundata, Halodule pinifolia, and Cymodocea serrulata. These species were found on sand substrates, with the highest total density and percentage cover observed at Station 5 (1135.22 ind/m2 and 40.74%). The results highlight the necessity for routine monitoring, mapping, and further research to comprehend seagrass population dynamics and support effective conservation policies. Implementation of recovery strategies, water quality management, and continued research support is imperative to ensure the sustainability of seagrass ecosystems and marine resources in Cempi Bay.